Municipal revenue over-budgeting: a dynamic analysis of its determinants - Jorge, Susana (2022)
This paper investigateswhich factors affect revenue over-budgeting in the local government,considering budgetary, political, and institutional determinants. It appliesdynamic panels analysis to data from Portuguese municipalities between 2005 and2017. Regarding budgetary arrangements, over-budgeting has implications forseveral years, taking up to three years to dissipate. The difference between budgetedrevenues and the ones collected in the previous year is a good predictor thatrevenue is overestimated. The ratio of own-source over total revenue isdirectly related with over-budgeting; however, this effect comes from the municipality’swealth. About political factors, municipal Executives with political majoritiesand in electoral years are more prone to over-budget; however, ideology does not seem to be important. Asfor institutional arrangements, participationin any debt restructuring program is inversely related to over-budgeting, whileexcessive debt does not seem to play any role. Overall, the only mechanismwhich reduces over-budgeting misbehavior is external control.